Developing a new industry (Paris, 1989)
This book introduce aquaculture an overview. Findings of the fisheries commitee's extended meeting on aquaculture. Aquaculture in the 1990s, country surveys.
Keywords: Nuôi trồng thủy sản,Aquaculture; Khía cạnh kinh tế,Economic aspects